EFL LEARNERS’ RELATIVE CLAUSES IN WRITING SHORT ENGLISH DESCRIPTIVE ESSAYS - Afdal Ade Hendrayana (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The role of relative/adjective clauses in introducing new information, connecting with given information in sentences structures plays role in constructing grammatical sentences and doing well communication to face the global challenge. While some EFL learners still have sufficient knowledge in using relative clauses so it is assumed that not all EFL learners know how to construct adjective clauses grammatically and understand cognitively. This study shows how learners construct relative clauses in writing short descriptive essay. What learners’ problems as effect of lack competence on English grammar rules and some deviation which is caused by the Indonesian interference in English use since two languages have different pattern are discussed in this study as well. Through the analysis of 40 pieces of learners’ short descriptive essay, it is found that basic forms of English relative clauses; distinguishing between the antecedent; typically in a main clause and the relative pronoun in the relative clauses, the difference grammatical roles of possessive relative, differences between restrictive and non-restrictive relative clauses with their separation markers are problems in using adjective clause. The analysis of the data and discussion in this study are based on the theories of English grammatical, especially learning EFL and this study is derived and further developed based on a research report conducted in 2012 and 2016.